Enhancement of barrier properties of cement mortar with graphene nanoplatelet. (October 2015) - Du, Hongjian; Pang, Sze Dai
Abstract: The transport properties of cement mortar with graphene nanoplatelet (GNP) are investigated experimentally in this study. GNP, a low cost carbon-based nano-sheet, was added to mortar at contents of 0, 2.5, 5.0 and 7.5%, by weight of cement. The water penetration depth, chloride diffusion coefficient and chloride migration were determined for cement mortar with GNP and compared with plain cement mortar specimens. Test results showed that the addition of 2.5% GNP can cause significant decrease of 64%, 70% and 31% for water penetration depth, chloride diffusion coefficient and chloride migration coefficients respectively. The reduced water and ions ingress can be partially attributed to a reduction in the critical pore diameter of about 30%. This refinement of the microstructure by the GNP is validated by the mercury intrusion porosimetry (MIP) results. The impermeable GNP also contributes to the reduced permeability due to the increased tortuosity against water and aggressive ions ingress.